Properties of Foods That Impact Appetite Regulation in Cats - Bosch, Guido; Gilbert, Myrthe; Beerda, Bonne (Frontiers in Animal Science, 2022)
Overweight and obesity are common in global pet cat populations which makes it important to understand how properties of food affect appetite (food motivation). In four experiments, we studied this by using a model of operant conditioning for assessing appetite in which cats could press a lever for food rewards. There was no effect of protein status on motivation for protein, when evaluated in a cross-over design with cats receiving low protein (LP) or high protein (HP) foods for 14 days. Cats obtained similar numbers of HP and LP rewards, irrespective of whether their daily food was HP or LP (mixed-effects model, P=0.550 for food × reward, P=0.151 for reward). High dietary protein reduced food motivation when we regressed protein levels in 12 commercial foods (12.0 to 27.4 g crude protein/MJ metabolizable energy; P=0.022) fed for 2 days and tested at 5 h postprandially on the third day whereas fiber levels were without effect (3.8 to 17.8 g non-starch polysaccharides/MJ; P=0.992). Dietary fiber may reduce appetite depending on its physicochemical properties and we tested the effect of a gelling fiber (alginate), viscous fiber (psyllium) and a fermentable fiber (inulin). Cats received test foods as well as control foods for 3 days and were tested on the third day at 3 h (alginate), 5 h (psyllium) or 8 h (inulin) postprandially. Enriching the food with alginate (P=0.379) or psyllium (P=0.153) did not affect the number of rewards obtained, but the feeding of the inulin-enriched food did make the cats obtain fewer rewards than when they received the control food (P=0.001). Finally, cooking or grinding of dietary meat increased the number of rewards obtained by cats, on day 3 at 3 h postprandial, without evidence for additive effects of these treatments (P=0.014 for grinding × cooking). This study shows that dietary content of protein or fiber, and the grinding or cooking of meat, all affect appetite in cats as expected, though some predicted effects remained undetected and clearly details regarding food properties matter. These and future findings can guide the designing of foods that promote satiety and prevent over-eating in meal-fed cats.